Optimalisasi Promosi Dan Pemasaran Produk Umkm Melalui Pembuatan Katalog Sebagai Strategi Penguatan Ekonomi Lokal Di Kelurahan Kedamaian - Sartika, Dewi; Imelia, Anti; Putri, Carissa Lilian; Munthe, Christiani Bertha Uli; Khairunisa, Intan; Dzaki, M Allan; Wibisono, M Rahid; Putri, Widya Dwi Astuti Rahma (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2026)
The UMKM product catalog creation program aims to improve UMKM players' understanding of promotion and marketing and strengthen the competitiveness of local products. Activities are carried out through the provision of promotional materials, assistance in catalog preparation, and the use of catalogs as a sustainable promotional medium. The results of the activities show a significant improvement in all aspects assessed. The understanding of UMKM players increased from 40% to 90%, ownership of promotional media from 30% to 85%, and completeness of product information from 35% to 88%. In addition, marketing reach increased from 25% to 80% and product competitiveness from 30% to 85%. This program has proven effective in increasing the percentage of UMKM promotion and marketing achievements in a sustainable manner.